John Thompson's modern course for the piano : the third grade book. Something new every lesson - Thompson, John 1889-1963 (The Willis Music, 1938)
Based on the fundamentals of interpretation: form, mood and style. Carries on without interruption the musicianship developed in the " Second Grade Book".